Spectroscopic study of a carbon pellet ablation cloud - Goto, M; Morita, S; Koubiti, M (Journal of physics. B, Atomic, molecular, and optical physics, 2010)
Carbon pellets were injected into high-temperature plasmas produced in the Large Helical Device (LHD), a heliotron-type fusion experimental device. Radiation from a high-density plasma formed around the pellet core, the so-called ablation cloud, was observed and its spectrum in the UV--visible wavelength range was obtained. The observed spectrum is found to be dominated by emission lines of CII and CIII ions, and their level populations are determined from the measured line intensities. The result suggests that LTE (local thermodynamic equilibrium) is established over the measured excited levels for both ions, and the electron temperature is determined to be 2.5 eV and 3.0 eV for the CII and CIII ions, respectively, on the assumption that level populations follow a Boltzmann distribution. For the plasma dominated by the CII lines, the electron density, ne = 6.5 X 1022 m-3, and plasma volume, V = 5.3 X 10-6 m3, are simultaneously derived from a fit of the CII Delta *l 723 nm ([1s22s2]3p 2Po--3d 2D) line profile which is subject to various broadening effects such as Stark broadening. For the plasma dominated by CIII lines, V = 4.5 X 10-2 m3 is derived from an analysis of the reabsorption effect appearing in fine structure lines of the CIII Delta *l 117 nm ([1s2]2s2p 3Po--2p2 3P) transition. The assumption of electric charge neutrality in the ablation cloud yields ne = 4.7 X 1020 m-3. These results suggest such a structure in the ablation cloud that a dense plasma dominated by the CII lines is surrounded by a larger and lower density plasma which is responsible for the CIII lines. The assumption of complete LTE for CIII levels, which is used in the analysis, is shown to be approximately true with the help of collisional-radiative model calculations, for which the reabsorption effect is taken into account. Thus, in this study various plasma parameters in the ablation cloud are determined and information about the cloud structure is obtained.